Pengaruh Tanaman Air Terhadap Kadar Fosfat Pada Kolam Fish Control IPAL RSUD Panembahan Senopati Bantul - Novi Ratnaningsih; Sardjito Eko Windarso; Urip Widjajono (Poltekkes Kemenkes Yogyakarta, 2011)
Waste water from hospital is one source of potential water pollutants and harmful to people. Based on the secondary data from the monitoring of effluent parameters in 2009, it was revealed that Panem-bahan Senopati Bantul District Hospital had phosphate content which still exceeded the standard. The purpose of this research was to know the effect of the water plants added in fish control pond for reducing the concentration of phospate by conducting an experiment with pre-test post-test with control group design. The water plants used were Eichornia crassipes, Pistia stratiotes and Ipomea aquatica which were acclimatized beforehand. The weight of the each plants were 400 grams/0,5 m3 and applied in 24 hour contact time. The p-values obtained from the t-test were 0,04 for Eichornia crassipes; 0,034 for Pistia stratiotes and 0.004 for Ipomea aquatica, which means that the pre and post phosphate concentrations were significant. The sub-sequent one-way anova test gained p-value of 0,008 which can be in-terpreted that the reduction among the three plants were significant.